Toe the line, break the whip: explaining floor dissent in parliamentary democracies. Issue 4 (4th July 2017) - Willumsen, David M.; Öhberg, Patrik
Abstract: This article analyses the drivers of individual dissent in floor voting in parliamentary regimes. It focuses on the effect of ideological heterogeneity in legislative parties on individual MPs' voting behaviour, as well as the different incentives caused by the differing consequences of defection and abstention. Combining individual-level survey and voting data from the Swedish Riksdag, neither of which is subject to selection bias, the study overcomes several limitations of previous research. It shows that MPs' decisions to dissent are partly driven by ideological differences with their party, but also by the imperatives of maintaining a government majority in a parliamentary regime, along with the level of influence MPs exert on legislation. It also highlights the importance of distinguishing between abstaining from voting and defecting. Merely pooling the two oversimplifies the behaviour of MPs.